Roles for Non-coding RNAs in Spatial Genome Organization - Khosraviani, Negin; Ostrowski, Lauren A.; Mekhail, Karim (Frontiers in Cell and Developmental Biology, 2019)
Genetic loci are non-randomly arranged in the nucleus of the cell. This order, which is important to overall genome expression and stability, is maintained by a growing number of factors including the nuclear envelope, various genetic elements, and dedicated protein complexes. Here, we review evidence supporting roles for non-coding RNAs (ncRNAs) in the regulation of spatial genome organization and its impact on gene expression and cell survival. Specifically, we discuss how ncRNAs from single-copy and repetitive DNA loci contribute to spatial genome organization by impacting perinuclear chromosome tethering, major nuclear compartments, chromatin looping, and various chromosomal structures. Overall, our analysis of the literature highlights central functions for ncRNAs and its transcription in the modulation of spatial genome organization and its connection to human health and disease.